Xpert Flu for point-of-care diagnosis of human influenza in industrialized countries. (May 2014) - Salez, Nicolas; Nougairede, Antoine; Ninove, Laetitia; Zandotti, Christine; de Lamballerie, Xavier; Charrel, Rémi N
<x xml:space="preserve">Abstract</x> Respiratory infections, particularly those caused by influenza viruses, represent the third-most important cause of death in the world due to infectious diseases. Nevertheless, despite the enormous publicity attracted by epidemics due to these viruses, laboratory diagnosis, documentation and recording of respiratory diseases is still unsatisfactory. Available diagnostic tests capable of providing results rapidly are either limited and insufficiently sensitive or highly sensitive and specific but insufficiently rapid. Considerable investment and research efforts have been made towards the development of new diagnostics for influenza A and B viruses and the Xpert® Flu assay (Cepheid®, CA, USA) has emerged as one of the most promising. In this article, we review current knowledge of the Xpert Flu test, discuss its potential value as a point-of-care test and outline the potential leads for future development.